2020
DOI: 10.1116/6.0000251
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependent luminescence and piezoelectricity in monolayer transition metal dichalcogenides

Abstract: The modification of optical and electronic properties of transition metal dichalcogenides via mechanical deformation has been widely studied. Their ability to withstand large deformations before rupture has enabled large tunability of the bandgap, and further, the spatially varying strain has been shown to control the spatial distribution of the bandgap and lead to effects such as carrier funneling. Monolayer transition metal dichalcogenides exhibit a significant piezoelectric effect that could couple to a spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…For the simulated linearly polarized Gaussian beam, the optical momentum flux points only out-of-plane in the direction of light propagation (Figure a). This qualitatively replicates the effects achieved by a physical push of monolayer WS 2 , for instance, similar to that generated by AFM tips in contact mode . For LG beams, the optical momentum flux density still has a significant out-of-plane component, but in addition there is an in-plane shear force, corresponding to the azimuthal component of the momentum flux (Figure b).…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…For the simulated linearly polarized Gaussian beam, the optical momentum flux points only out-of-plane in the direction of light propagation (Figure a). This qualitatively replicates the effects achieved by a physical push of monolayer WS 2 , for instance, similar to that generated by AFM tips in contact mode . For LG beams, the optical momentum flux density still has a significant out-of-plane component, but in addition there is an in-plane shear force, corresponding to the azimuthal component of the momentum flux (Figure b).…”
Section: Resultsmentioning
confidence: 68%
“…This effect is most pronounced for the exfoliated sample, with the PL spectra returning to close to its initial line shape after 2 hours (Figure S11). Previous work has demonstrated that the X 0 component red shifts and the T/X 0 intensity ratio increases with strain caused by out-of-plane deformations, such as wrinkles . Due to the faster relaxation times displayed by WS 2 samples compared to graphene, wrinkling cannot be monitored directly with AFM and Raman mapping.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This qualitatively replicates the effects achieved by a physical push of monolayer WS2, for instance, similar to that generated by AFM tips in contact mode. 43 For LG beams, the optical momentum flux density still has a significant out-of-plane component, but in addition there is an in-plane shear force, corresponding to the azimuthal component of the momentum flux (Fig. 5d).…”
Section: Numerical Simulations Of Optical Forces and Torquesmentioning
confidence: 97%
“…Previous work has demonstrated that the X 0 component red shifts and the T/X 0 intensity ratio increases with strain caused by out-of-plane deformations, such as wrinkles. 43 Due to the faster relaxation times displayed by WS2 samples compared to graphene, wrinkling cannot be monitored directly with AFM and Raman mapping. The residual spectral changes after switching back from LG to Gaussian beams rules out the possibility of an electronic origin of the effect.…”
Section: Monolayer Ws2mentioning
confidence: 99%